Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

1. Simplify: \(2 \times (7 + 5) + 3\)

2. Simplify: \(4 \times (5 \times 2) + (7 \times 2) = (3 \times 5) + 45\)

3. Simplify: \(8 \times (9 - 6) - (10 - 5)\)

4. Simplify: [tex]\(10 \times 6 + 7 \times 10 - 70 \times 0 + 4\)[/tex]


Sagot :

Alright, let's solve each expression step by step:

1. Expression: \(2 \times (7 + 5) + 3\)
- First, calculate the value inside the parentheses: \(7 + 5 = 12\).
- Next, multiply the result by 2: \(2 \times 12 = 24\).
- Finally, add 3 to the result: \(24 + 3 = 27\).

So, \(2 \times (7 + 5) + 3 = 27\).

2. Expression: \(4 \times (5 \times 2) + (7 \times 2) = (3 \times 5) + 45\)
- First, simplify both sides of the equation independently to check for equality.
- Left side:
- Calculate inside the parentheses: \(5 \times 2 = 10\).
- Then, multiply by 4: \(4 \times 10 = 40\).
- Add the product of \(7 \times 2\): \(40 + 14 = 54\).
- Right side:
- Calculate the products separately: \(3 \times 5 = 15\) and just add 45.
- Add them together: \(15 + 45 = 60\).
- Now compare both sides: \(54 \neq 60\).

Therefore, the equation \(4 \times (5 \times 2) + (7 \times 2) \neq (3 \times 5) + 45\) is False.

3. Expression: \(8 \times (9 - 6) - (10 - 5)\)
- First, calculate the values inside the parentheses:
- \(9 - 6 = 3\)
- \(10 - 5 = 5\)
- Next, multiply by 8: \(8 \times 3 = 24\).
- Finally, subtract the second result: \(24 - 5 = 19\).

So, \(8 \times (9 - 6) - (10 - 5) = 19\).

4. Expression: \(10 \times 6 + 7 \times 10 - 70 \times 0 + 4\)
- First, calculate each multiplication:
- \(10 \times 6 = 60\)
- \(7 \times 10 = 70\)
- \(70 \times 0 = 0\)
- Next, add all the results: \(60 + 70 + 0 + 4 = 134\).

So, \(10 \times 6 + 7 \times 10 - 70 \times 0 + 4 = 134\).

In summary:
1. \(2 \times (7 + 5) + 3 = 27\)
2. \(4 \times (5 \times 2) + (7 \times 2) \neq (3 \times 5) + 45\) is False
3. \(8 \times (9 - 6) - (10 - 5) = 19\)
4. [tex]\(10 \times 6 + 7 \times 10 - 70 \times 0 + 4 = 134\)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.